PERAN BRAND IMAGE MEMEDIASI PENGARUH HARGA TERHADAP KEPUTUSAN PEMBELIAN DI MASA PANDEMI (Studi Pada Produk Smartphone Xiaomi di Kota Denpasar) - Katu, Geldy Mahantara Kristindo; Suparna, Gede (E-Jurnal Manajemen, 2022)
This study aims to explain the effect of price on purchasing decisions mediated by brand image. This research was conducted on consumers of Xiaomi smartphone products in Denpasar City. The number of samples taken as many as 100 respondents, with a non-probability sampling technique of determining the sample using the purposive sampling method. Data collection was done through a questionnaire. The analysis technique used is Partial Least Square (PLS). Based on the results of the analysis, it was found that price and brand image have a positive and significant effect on purchasing decisions. This shows that the more affordable the price and the better the brand image, the higher the consumer's purchase decision. Price partially has a significant effect on purchasing decisions. These results mean that an affordable price can improve the purchasing decision of Xiaomi smartphones. Brand image also partially has a significant effect on purchasing decisions, which can be concluded that the existence of a good brand image can improve purchasing decisions. Keywords: price, brand image, purchase decision